An empirical test of calendar effects in Vietnam stock market - Le, Phuong Lan; Do, Duy Tan (Journal of International Economics and Management, 2016)
This paper examines five popular calendar effects using closing prices of VN – Index over the period 2000 – 2014. Results of OLS regression show that while there is little evidence confirming the existence of some seasonal anomalies like weekend, January and Halloween effects, holiday and TOM effects assuredly exist on HOSE. One interesting finding is that there is some evidence for the presence of Tuesday effect. To specify, over the subperiod 2010 – 2014, the mean return for Tuesday is significantly negative and all mean returns for Wendnesday, Thursday and Friday are significantly higher than that for Tuesday. These findings provide additional international evidence for seasonal anomalies.